2010
DOI: 10.1007/s12026-010-8168-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated immune dysfunction and viral infection: role in the pathogenesis of AIDS-related lymphoma

Abstract: HIV infection is associated with a much higher risk for the development of non-Hodgkin lymphoma (AIDS-NHL). The principal causes of lymphomagenesis in HIV-infected individuals are thought to be the loss of immune function seen in HIV infection, which results in the loss of immunoregulation of Epstein–Barr virus-infected B cells, as well as HIV infection-associated immune dysregulation, including chronic B-cell activation. In this review, we discuss recent reports that further support the importance of these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 94 publications
1
83
0
1
Order By: Relevance
“…HIV-NHLs derived from either germinal or postgerminal center B lymphocytes are often characterized by clinical aggressiveness and display a predilection for extranodal sites (3)(4)(5). To date, the usual reason for the increase of HIV-NHL is said to be an HIV-1-driven immune dysfunction (6). The onset of HIV-NHL is often preceded by an overproduction of B-cell stimulatory cytokines, which further sustains B-cell activation and possibly drives the generation of activation-induced DNA modification errors and oncogenic translocations, conferring the transformed phenotype to B cells (7).…”
Section: B-cell Clonogenicitymentioning
confidence: 99%
“…HIV-NHLs derived from either germinal or postgerminal center B lymphocytes are often characterized by clinical aggressiveness and display a predilection for extranodal sites (3)(4)(5). To date, the usual reason for the increase of HIV-NHL is said to be an HIV-1-driven immune dysfunction (6). The onset of HIV-NHL is often preceded by an overproduction of B-cell stimulatory cytokines, which further sustains B-cell activation and possibly drives the generation of activation-induced DNA modification errors and oncogenic translocations, conferring the transformed phenotype to B cells (7).…”
Section: B-cell Clonogenicitymentioning
confidence: 99%
“…40 This environment with dysregulated cytokine/chemokine release and B-cell hyperstimulation 41 along with the presence of concomitant infection (eg, Epstein-Barr virus, human herpesvirus type 8, cytomegalovirus) may promote a permissive environment for HIV-1-induced B-cell expansion and impaired immune surveillance, culminating in lympho-proliferative disorders. 42 Up until now, the molecular mechanisms responsible for B-cell transformation associated with ARLs have not been elucidated. However, in this respect it is worth noting that recent data have highlighted a role for p17 variants in promoting B-cell growth and malignant transformation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during HIV infection, altered immune responses including chronic B cell activation has been reported [39]. It has been suggested that combination of highly regulated latent infection of EBV in B cell and chronic reactivation of replication in lymphoid tissue and mucosal surfaces may 7 lead to many patterns of virus-host interaction, which may reveal important strategies of EBV mediated immune evasion [85].…”
Section: B Cell Response During Viral Infectionmentioning
confidence: 99%